PENGARUH PENAMBAHAN SERBUK DAUN KAYU MANIS (Cinnamomum burmanii) PADA PAKAN TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Moh. Fikri Ubaidillah; Farikhah Farikhah; Firma Fika Rahmawati (Universitas Muhammadiyah Gresik, 2018)
The use of phytopharmaca is not well known to all tilapia farmers, especially in Gresik Regencywhich is partly cultivation of Oreochromis niloticus tilapia fish.Demand for tilapia in the marketis quite high as the number of restaurants that make tilapia as one of the menu.Cinnamomumburmanii, cinnamon leaf powder is dried and crushed and easy enough to make it effectivelycheaper than chemicals that are expensive enough to improve the survival and growth oftilapia.This study aims to determine the best dosage of the addition of Cinnamomum burmanii,cinnamon leaf powder.The method used was complete random design (CRD) with treatment ofdose of cinnamon leaf dose (control), 0.25%, 0.5%, 1%/kg of feed per treatment consisted of 3replications.Parameters observed for survival, absolute weight and daily growth rate. The resultsof this study showed that the best dosage of cinnamon leaf powder had a significant effect onsurvival, absolute weight and daily growth rate of tilapia.The best dosage is the addition ofcinnamon leaf powder for survival, absolute weight and daily growth rate at a dose of 0.25%/kgof feed.